Dynamics of Tethered Satellite Systems. - Aslanov, V. S.; Ledkov, A. S.; ScienceDirect eBooks (Burlington : Elsevier Science, 2012)
Aimed at engineering students and professionals working in the field of mechanics of space flight, this book examines space tether systems - one of the most forward-thinking directions of modern astronautics. The main advantage of this technology is the simplicity, profitability and ecological compatibility: space tethers allow the execution of various manoeuvers in orbit without costs of jet fuel due to the use of gravitational and electromagnetic fields of the Earth. This book will acquaint the reader with the modern state of the space tether's dynamics, with specific attention on the resear.
4.5 References5 Use of chaotic dynamics for the analysis of tether system motion; 5.1 Some elements of chaotic dynamics; 5.2 The chaotic approach in STS dynamics; 5.3 References; Conclusion; Index.
Print version record.
Includes bibliographical references and index.
Elsevier
Keywords: Tethered satellites; Tethered space vehicles -- Dynamics; TECHNOLOGY & ENGINEERING -- Engineering (General); Tethered satellites; Tethered space vehicles -- Dynamics; Electronic books